2018
DOI: 10.3390/nu10040445
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Ellagitannin-Rich Strawberry Extracts on Biochemical and Metabolic Disturbances in Rats Fed a Diet High in Fructose

Abstract: The present study compares the effects of two dietary strawberry extracts rich in monomeric (ME) or dimeric (DE) ellagitannins (ETs) on gastrointestinal, blood and tissue biomarkers in Wistar rats fed high-fructose diets. Both strawberry extracts beneficially affect the antioxidant status and lipid profile of the liver and serum. The ME extract shows a greater ability to inhibit lipid peroxidation in kidneys, more effectively decreases serum and liver triglycerides, and exerts greater anti-inflammatory effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…Dietary supplementation of raw CBE significantly decreased the concentration of TBARS in heart of high-fat groups. Similar results were obtained in studies of other authors [64,65]. Many studies have shown that cocoa and cocoa products can exert strong antioxidant properties and improve resistance to oxidative stress [7].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Dietary supplementation of raw CBE significantly decreased the concentration of TBARS in heart of high-fat groups. Similar results were obtained in studies of other authors [64,65]. Many studies have shown that cocoa and cocoa products can exert strong antioxidant properties and improve resistance to oxidative stress [7].…”
Section: Resultssupporting
confidence: 87%
“…D RT diet also significantly increased the release degree of β-galactosidase, compared to all other groups. The obtained results are confirmed by literature data indicating that supplementation with polyphenolic-rich extracts advantageously modulates the enzymatic activity of the cecum microbiota [63,64]. 67.9 ± 0.9 a 69.6 ± 1.4 a 64.9 ± 1.5 a 83.9 ± 1.4 b 0.008 β-glucuronidase Extracellular 1 13.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In the urine, the predominant metabolites were glucuronidated urolithin A and nasutin A. It has been reported that glucuronidation enhances the solubility of these molecules and facilitates their urinal excretion [Fotschki et al, 2018].…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the chemical structure of ET and subsequently that of ET metabolites largely depends on the plant source [Landete, 2011;Karlińska et al, 2019]. The main strawberry ET is agrimoniin, a GOG-type dimer composed of two α-1-O-galloyl-2,3:4,6--bis-hexahydroxydiphenoyl-D-glucose units linked by a C-O-C bond between two gallic acid residues [Fotschki et al, 2018;Chiabrando et al, 2018;Nowicka et al, 2019]. The presence of sanguiin H-6 and lambertianin C, but as minor ET, has been also detected in strawberry fruit [Vrhovsek et al, 2012].…”
Section: Introductionmentioning
confidence: 99%